Preparing for Future Adversities: Lessons From the COVID-19 Pandemic in Australia for Promoting Relational Resilience in Families - Biden, Ebony J.; Greenwood, Christopher J.; Macdonald, Jacqui A.; Spry, Elizabeth A.; Letcher, Primrose; Hutchinson, Delyse; Youssef, George J.; McIntosh, Jennifer E.; Olsson, Craig A. (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic has placed considerable pressure on families, testing the quality of relationships and the strength of social support within and beyond the family network. However, little is known about the pre-pandemic factors that predict family relational resilience and social functioning during times of natural disaster or global crisis. Here we use data from one of Australia’s longest running studies of social and emotional development to examine the nature and timing of possible relational and social support intervention aimed at preparing families for future adversities. Methods: Data were from the Australian Temperament Project Generation 3 (ATPG3) Study, an intergenerational cohort of families, following three generations since 1983. A subset of Generation 2 parents completed a COVID-19 specific survey in May-September 2020 (502 parents of 871 children; 60% mothers; 37-38 years). These participants had completed the Quality of Relationships Inventory to assess social support during young adulthood, at 23-24 years (2006) and 27-28 years (2010), before next generation conception. Participants had also completed the Maternity Social Support Scale one year postpartum for each child born across the ATPG3 assessment period (2012-2019). In 2020, during the height of the Australian lockdowns, participants rated the quality of their relationships with their partners, children and broader family and friends, in addition to social support within and extended beyond their family. Results: Pre-pandemic partner support was associated with partner relationship quality during the pandemic (β = 0.22). Pre-pandemic support from friends was associated with relationship quality with other family and friends during the pandemic (β = 0.12–0.18). Pre-pandemic support (from partner, family and friends) was consistently associated with social support within families during the pandemic (β = 0.11–0.21). Pre-pandemic support from friends was also associated with family support extended to others within their local community during the pandemic (β = 0.12–0.13). Conclusions: Strengthening supportive relationships during major life transitions, prior to the start of family life and in early parenthood, may have long-term and intergenerational benefits years into the future for both families and communities. This may promote resilience during future crises and other more normative stressful life events.